Utility, rights and Relativity: A Preliminary Look at Lawyers in Hard Cases - PHANG, Andrew B.L. (Institutional Knowledge at Singapore Management University, 1993)
The following article was written several years ago; its objective (as the opening paragraphs suggest) was to set forth, in as simple a form as possible, the basic philosophical as well as ethical dilemmas and issues confronting lawyers. The audience initially targeted comprised practitioners. The manuscript has, however, stayed on the shelf, gathering dust. I can think of no clear reason for this. Perhaps it was because of the preachiness inherent within the purpose. Perhaps it was because it did not really add anything remarkably new to the literature on the subject - a great stumbling block to writers, despite the avowed purpose of the piece which I have just briefly described.